1989
DOI: 10.1002/ccd.1810170213
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of iced and room temperature injectate for thermodilution cardiac output

Abstract: Cardiac output estimation by thermodilution is carried out using room temperature or iced injectate, but the accuracy and variability of the two methods is not well documented. Room temperature and iced injectate were compared in 21 patients undergoing diagnostic cardiac catheterization. Dextrose injectate (10 ml) was administered in prefilled syringes left to stand either in iced water or in room air. Four injections were made sequentially with room temperature and iced injectate. Cardiac output by room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Similar finding was noted also by Runciman et al in a previous large animal study. Bourdillon and Fienberg found that there was variation in the measurements obtained by R‐TDCi and C‐TDCi. An average of seven measurements of R‐TDCi when compared to an average of four measurements of C‐TDCi were used to decrease variability.…”
Section: Discussionmentioning
confidence: 99%
“…Similar finding was noted also by Runciman et al in a previous large animal study. Bourdillon and Fienberg found that there was variation in the measurements obtained by R‐TDCi and C‐TDCi. An average of seven measurements of R‐TDCi when compared to an average of four measurements of C‐TDCi were used to decrease variability.…”
Section: Discussionmentioning
confidence: 99%
“…Although room-temperature and iced injectates have been compared in numerous studies, [1][2][3][4][6][7][8][9][10][11][12][13][14][15][16][17] many of the studies had deficiencies that make generalization of their findings difficult. Some of the studies used an open system (individual syringes filled with fluid) to deliver the injectates, a practice that was common at one time, [2][3][4][10][11][12][14][15][16] or did not describe the delivery system.…”
Section: Room-temperature Vs Iced Injectatesmentioning
confidence: 99%
“…Some of the studies used an open system (individual syringes filled with fluid) to deliver the injectates, a practice that was common at one time, [2][3][4][10][11][12][14][15][16] or did not describe the delivery system. 1,3,8,17 Very few studies have examined the accuracy of measurements made with room-temperature injectate in closed injectate delivery systems.…”
Section: Room-temperature Vs Iced Injectatesmentioning
confidence: 99%
See 1 more Smart Citation